CORPUS UTILITY IN TEACHING LEGAL ENGLISH VOCABULARY TO LAW STUDENTS - Nhạc, Hương Thanh (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2025)
Corpora usage has been increasingly employed in facilitating specialized English for students in English-for-specific-purposes classes. This paper focuses on the application of a corpus-based approach as a supplementary method to traditional ones in instructing legal English vocabulary in terms of its meaning and collocations to law students in Vietnam. To achieve this aim, a group of 29 students of the experimental group was assigned to corpus-based work along with a traditional teaching method, while 27 students in the control group experienced the sole later one in legal English classes during 15 weeks. The pedagogical experiment, as well as the assessment and scoring criteria, were discussed and presented at the beginning of the course. Participants’ tests, survey questionnaires, and focus-group discussions were utilized as the data collection instruments to ensure triangulation and a multidimensional analysis of the research issue. Results demonstrated that the experimental group performed much better than the control group in terms of vocabulary understanding and interpretation, as well as collocations. Students of the treatment group also showed positive attitudes, acknowledging the potential benefits of the corpus-based approach for language-related enhancement in their future profession.